2015
DOI: 10.1371/journal.pone.0119785
|View full text |Cite
|
Sign up to set email alerts
|

The Flavoproteins CryD and VvdA Cooperate with the White Collar Protein WcoA in the Control of Photocarotenogenesis in Fusarium fujikuroi

Abstract: Light stimulates carotenoid biosynthesis in the ascomycete fungus Fusarium fujikuroi through transcriptional activation of the structural genes of the pathway carRA, carB, and cart, but the molecular basis of this photoresponse is unknown. The F. fujikuroi genome contains genes for different predicted photoreceptors, including the WC protein WcoA, the DASH cryptochrome CryD and the Vivid-like flavoprotein VvdA. We formerly found that null mutants of wcoA, cryD or vvdA exhibit carotenoid photoinduction under co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…Although the ΔvvdA mutant accumulates less pigment during the second phase, the rate and peak of the first phase is actually higher than wild type. This suggests that VvdA may inhibit WcoA activity early in the light response, in partial agreement with its function in N. crassa (Castrillo and Avalos, 2015). A direct interaction between the two proteins has yet to be experimentally determined.…”
Section: Is There a Model For Fungal Photobiology?mentioning
confidence: 62%
See 3 more Smart Citations
“…Although the ΔvvdA mutant accumulates less pigment during the second phase, the rate and peak of the first phase is actually higher than wild type. This suggests that VvdA may inhibit WcoA activity early in the light response, in partial agreement with its function in N. crassa (Castrillo and Avalos, 2015). A direct interaction between the two proteins has yet to be experimentally determined.…”
Section: Is There a Model For Fungal Photobiology?mentioning
confidence: 62%
“…Furthermore, deletion of the cryptochrome ortholog, cryD , in F. fujikuroi leads to reduced light-induction of carotenoid genes. While this in some ways reflects the signaling role of CryA seen in A. nidulans , it is the first report of a cryptochrome regulating carotenoid biosynthesis (Castrillo and Avalos, 2015). …”
Section: Is There a Model For Fungal Photobiology?mentioning
confidence: 81%
See 2 more Smart Citations
“…Previous studies showed that the DASH‐type cryptochrome CryD plays a light‐dependent regulatory role in secondary metabolism and development in Fusarium fujikuroi and is involved in the photoinduction of carotenoid biosynthesis in this fungus . Here, we have heterologously expressed this protein and studied its spectroscopic and biochemical properties after purification.…”
Section: Introductionmentioning
confidence: 99%